2022
DOI: 10.7150/thno.72037
|View full text |Cite
|
Sign up to set email alerts
|

DCLK1 promotes colorectal cancer stemness and aggressiveness via the XRCC5/COX2 axis

Abstract: Rationale: Doublecortin-like kinase 1 (DCLK1) is a serine/threonine kinase that selectively marks cancer stem-like cells (CSCs) and promotes malignant progression in colorectal cancer (CRC). However, the exact molecular mechanism by which DCLK1 drives the aggressive phenotype of cancer cells is incompletely determined. Methods: Here, we performed comprehensive genomics and proteomics analyses to identify binding proteins of DCLK1 and discovered X-ray repair cross-complementing 5 (XRCC5). Thus, we explored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…been described in their regulation of prostaglandins, while little to no research is available on the other LM classes [42][43][44][45]. Mef2a and Mef2c have been identified as downstream effectors of PGE2, which could indicate a feedback loop on prostaglandin e synthesis [46,47].…”
Section: Cell-type-specific Gene Regulationmentioning
confidence: 99%
“…been described in their regulation of prostaglandins, while little to no research is available on the other LM classes [42][43][44][45]. Mef2a and Mef2c have been identified as downstream effectors of PGE2, which could indicate a feedback loop on prostaglandin e synthesis [46,47].…”
Section: Cell-type-specific Gene Regulationmentioning
confidence: 99%
“…DCLK1 is an enzyme that regulates epithelial mesenchymal transition ( 43 ). Mesenchymal DCLK1 labeling of tumor stem cells in a genetic mouse model of CRC ( 44 ). DCLK1-targeted CAR-T cells therapy inhibited xenograft tumor growth in mice without apparent toxicity ( 45 ).…”
Section: Basic Experimental Of Car-t Cells Therapy For Crcmentioning
confidence: 99%
“…Recently, DCLK1 has been reported to play an important role in inflammatory diseases. Kim et al ( 2022 ) reported that DCLK1 promotes colorectal cancer by generating an inflammatory tumor microenvironment. Roy et al ( 2021 ) determined that the Notch‐DCLK1 axis is integral to colitis progression.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a number of studies have shown a range of DCLK1 activities in tumorigenesis (Sureban et al, 2014;Chandrakesan et al, 2017). Increased levels of DCLK1 have also been reported in various human cancers (Nevi et al, 2021;Kim et al, 2022). Recently, DCLK1 has been reported to play an important role in inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%